Modelling of transient flow of piston ring-liner contact using synthetic lubricants. (October 2022) - Zavos, Anastasios; Nikolakopoulos, Pantelis G
The paper contains the results of the transient flow of piston ring conjunction of a single-cylinder motorbike engine. Calculations of piston ring forces, asperity contact and gas blow-by are determined in computational fluid dynamics. The stochastic model of Greenwood-Tripp approach is used to predict the load of asperities. The hydrodynamic friction is also calculated by means of computational fluid dynamics including the multi-phase flow through Rayleigh–Plesset equation and a discrete phase model for simulating nanoparticles interaction. The major contribution of this analysis is to specifically investigate the impact of the lubricant with additives and the corresponding transient effects such as hydrodynamic pressure, cavitation and lubricant film within the contact. The results indicate that to investigate realistic mechanisms of multi-phase flow in piston ring-liner contact, the contribution of nanoparticles should be matched with the type of lubricants. In addition, this advanced computational fluid dynamics model showed that nanoparticles motion is important in reciprocating line contacts, leading to lower boundary friction in the order of 8.8% than a simple model where cavitation and nanoparticles are ignored.